Testate Amoeba Species- and Trait-Based Transfer Functions for Reconstruction of Hydrological Regime in Tropical Peatland of Central Sumatra, Indonesia - Krashevska, Valentyna; Tsyganov, Andrey N.; Esaulov, Anton S.; Mazei, Yuri A.; Hapsari, Kartika Anggi; Saad, Asmadi; Sabiham, Supiandi; Behling, Hermann; Biagioni, Siria (Frontiers in Ecology and Evolution, 2020)
Tropical peatlands play an important role in carbon storage and in water regulation on a landscape level. However, our understanding of their ecology and long-term hydrological dynamics remains limited. Transfer functions, constructed on the basis of biological indicators (proxies) with known ecological preferences, allow us to infer past environmental conditions and serve as a basis for prediction of future changes in peatlands. Here, we use testate amoebae to develop the first species- and functional trait-based transfer functions for the Southeast Asia. This provides a valuable tool for future reconstructions of past hydrological changes in tropical peatlands, their development, and climatic changes. Surface samples for testate amoeba analysis were taken in various biotopes along two transects across the Sungai Buluh peatland in Central Sumatra. The following environmental characteristics were measured: water table depth (WTD), light intensity, pH, total C and N concentrations. The analysis of the surface samples revealed 145 morphotypes of testate amoebae belonging to 25 genera. A significant fraction of the variance in testate amoeba morphotypes and functional trait composition was explained by WTD and pH. The wide WTD range (0 to 120 cm) seems more valuable for reconstruction than the extremely short pH gradient (2.5 to 3.8). Thus, transfer functions were developed only for WTD, basing on weighted averaging model for morphotypes and multiple linear regression for functional traits. Both species- and trait-based model have a predictive ability for WTD reconstruction. For traits, the best performance of the model was reached by including five morphological traits: shell width, aperture shape, aperture invagination, shell shape and shell compression. We discuss the ecology of several taxa and highlight the traits, which reflect hydrological changes in this system. Though the hydrological preferences of some species are similar to those in high and middle latitude peatlands, we argue that latitudinal differences in morphospecies composition and variations in environmental relationships of species require the development of region-specific transfer functions. Moreover, our results indicate that ecological preferences of morphotypes within morphospecies also need to be considered and included in future studies.